Impact of environmental change on stability and conflict potentials in China - Heberer, Thomas; Senz, Anja-Désirée (Coping with Global Environmental Change, Disasters and Security, 2011)
During the last decades China has faced serious environmental degradations due to extensive economic development. In particular China’s large emissions of greenhouse gases have raised international concerns about the environmental situation in China. The country faces a large amount of international criticisms due to its poor environmental performance and is perceived as one of the most polluted countries in the world. The 2008 Environmental Performance Index Report of Yale University, which evaluates indicators like people’s health, air and water pollution, ranks China as 104 of 149 countries. According to the World Bank, the majority of the world’s most polluted cities are located in China (Klein 2004: 21).
Gesehen am 08.08.2019